2020
DOI: 10.18683/germs.2020.1180
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, characterization and antimicrobial resistance of Listeria monocytogenes isolated from beef meat in Meknes city, Morocco

Abstract: Introduction Listeria monocytogenes is one of the most pathogenic bacteria related to the consumption of contaminated food. This study aims to determine the prevalence of L. monocytogenes in raw beef meat in Meknes city of Morocco, to evaluate its pathogenicity and resistance to antimicrobials.Methods During four seasons, a total of 140 samples were collected from supermarkets, butcheries and Souk (weekly traditional market). The PCR method was used to examine the presence of specific and virulence genes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Studies from other countries include the research by Teixeira et al (2020) who reported the presence of L. monocytogenes in 12% (6/50) of beef samples in Brazil. Boukili et al (2020) detected L. monocytogenes in 7.14% (10/140) of analyzed beef meat samples in Morocco. Zhang et al (2021) determined that L. monocytogenes was present in 29.29% (70/239) of raw, intermediate and end meat products, and in 12.2% (29/239) of meat contact surface samples such as the floor, walls, transport units, pipes, trash can and weighing equipment, as well as the hands, clothes, and shoes of the handlers in Shanghai.…”
Section: Discussionmentioning
confidence: 97%
“…Studies from other countries include the research by Teixeira et al (2020) who reported the presence of L. monocytogenes in 12% (6/50) of beef samples in Brazil. Boukili et al (2020) detected L. monocytogenes in 7.14% (10/140) of analyzed beef meat samples in Morocco. Zhang et al (2021) determined that L. monocytogenes was present in 29.29% (70/239) of raw, intermediate and end meat products, and in 12.2% (29/239) of meat contact surface samples such as the floor, walls, transport units, pipes, trash can and weighing equipment, as well as the hands, clothes, and shoes of the handlers in Shanghai.…”
Section: Discussionmentioning
confidence: 97%
“…Так, якщо виявляють тільки ген lmo0737, то такий ізолят відносять до серотипу 1/2а або 3a, а наявність тільки гена ORF2819 -до 1/2b, 3b або 7. До серотипів 1/2c або 3c можна віднести лістерії, в яких виявлено гени lmo0737 та lmo1118, а якщо ORF2819 та ORF2110 -до 4b, 4d або 4e [4,7,23].…”
Section: полюшко д п стегній б т марченко н в болотін в іunclassified